GAMBARAN INDEKS DMF-T PADA ANAK DOWN SYNDROME DI SLB BCD-AUTIS AZ ZAKIYAH KOTA BANDUNG (Jurnal Kesehatan Siliwangi, 2020)
Tooth decay in Indonesia is included in the high category, especially in West Java, the problem of tooth decay, cavities or toothache in Indonesia is high. So far cavities remained a health problem in children. Especially for children with Down syndrome, namely children who have physical and psychological developmental limitations due to genetic disorders before they are born. This study aims to determine the description of the DMF-T index in children with Down syndrome. This type of research is descriptive. The sampling technique was accidental sampling in children with Down Syndrome in SLB Az Zakiyah, Bandung. Data is processed and presented in the form of frequency distribution tables. The results showed that the value of decay was 11, did not have missing values, had no filling value, the average DMF-T index in children with Down syndrome in SL Z Azakiyah Bandung with a score of 1.8 according to WHO included in the low category, and had a caries prevalence of 83.3%. Keywords: Down Syndrome and DMF-T Index